2021
DOI: 10.1192/bjo.2021.1003
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trials of antidepressant and anti-anxiety medications for people with autism spectrum disorder: systematic review and meta-analysis

Abstract: Background Although widely used, the current evidence for the efficacy of antidepressant and anti-anxiety medications for people with autism spectrum disorder (ASD) is limited and conflicting. Aims We carried out a systematic review and meta-analysis of randomised controlled trials that assessed the effectiveness of these medications in people with ASD. Method We searched the following databases: Cochrane Library, Medline, EMBASE, CINAHL, PsycINFO, ERIC, DARE and Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…In terms of pharmacological interventions, this review found that some medications (ADH, MDMA, SNRI) were associated with increased adverse events, although there is no evidence these medications improve mental health. This is in line with existing meta-analyses that suggest that the evidence for the use of antidepressants or anti-anxiety medications in autistic people is inconsistent ( D’Alò et al, 2021 ; Deb et al., 2021 ), and antipsychotics are not effective for anxiety or depression ( D’Alò et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In terms of pharmacological interventions, this review found that some medications (ADH, MDMA, SNRI) were associated with increased adverse events, although there is no evidence these medications improve mental health. This is in line with existing meta-analyses that suggest that the evidence for the use of antidepressants or anti-anxiety medications in autistic people is inconsistent ( D’Alò et al, 2021 ; Deb et al., 2021 ), and antipsychotics are not effective for anxiety or depression ( D’Alò et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…School-based interventions for anxiety show some promise for improving anxiety, although further evidence is needed. Finally, evidence for the use of anti-anxiety medications in autistic people is inconsistent (D'Alò et al, 2021;Deb et al, 2021). only a short period of time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 A 2021 systematic review on 13 RCTs on antidepressants and two on anxiolytics observed contradictory results on efficacy; their meta-analysis demonstrated no significant inter-group difference between the placebo and antidepressants in children. 7 An alternative approach, cognitive-behavioural therapy (CBT), can be effective but requires modification for those with ASD. 8 …”
mentioning
confidence: 99%